Residents’ Perception and Tourism Participation in Braga Street: The Mediating Role of Socio-Cultural Impact - Valerie Avrilia Zahra Maharani; Rini Andari; Masroulina Sevtiani (Lasigo Akademia Indonesia, 2026)
This study aims to examine a novel perspective by positioning socio-cultural impact as mediating mechanism linking residents’ perception and tourism participation in sustainable tourism participation in sustainable tourism development. While prior studies have examined several aspects of sustainability, this study focuses solely on socio-cultural aspect of sustainable tourism. A quantitative approach was collected from 243 total of local residents who have experienced the impacts of tourism development in the area. The data were analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) with AMOS and SPSS. The findings indicate that residents’ perception has a strong positive and significant effect on socio-cultural impact and also directly influences tourism participation. Socio-cultural impact further shows a significant positive effect on residents’ perception and tourism participation, acting as a partial mediator. The findings indicated that positive socio-cultural outcomes such as cultural preservation, community pride and improved quality of life played a crucial role in creating favorable perceptions and encouraging residents’ participation in tourism development.